Successful partnerships with third sector organisations to enhance the healthcare student experience: A partnership evaluation. (March 2015) - Bell, Katie; Tanner, Judith; Rutty, Jane; Astley-Pepper, Maxine; Hall, Richard
Summary There is limited research surrounding academic partnerships and more research is needed to educate universities, and the private, public and third sectors about the benefits and limitations of such partnerships. The aim of this study was to outline the unique partnership between Macmillan Cancer Support and De Montfort University and to evaluate the progress of this partnership. A qualitative approach was employed which involved interviews with nine members of the partnership's steering group. Interviews were transcribed and analysed using thematic analysis. The results showed that a partnership between a university and a third sector charity can have mutual benefits for all those involved, particularly for students and those affected by cancer. Furthermore, the module to develop volunteering among families affected cancer, created through this partnership is now being considered by other universities as a way of providing holistic and non-traditional lecture based learning experiences. Recommendations are made for future partnerships between third sector charities and universities.